The elf express - Lampard, Frank (London: Little, Brown Books for Young Readers, 2016)
"Frankie and his team love playing football. There's always time for a game - even at Christmas! Frankie and his friends are spending Christmas in Austria with his pen pal Heidi. He is excited to learn how to ski, even if it's not quite the same as playing football. Late on Christmas Eve they discover a lost elf who needs help. Frankie's team will need to use all their skills to get the elf back to his world, and return in time for Christmas!"--Publisher description
Keywords: Soccer stories